Decision Support System for Selection of the Best Member at Junjung Biru Waste Bank Using the Composite Performance Index (CPI) - Fitri Purwaningtias; Maria Ulfa; Febi Franata (Department of Informatics, Universitas Muhammadiyah Surakarta, Indonesia, 2020)
Junjung Biru Waste Bank conducts a selection of the best member biennially. The process is crucial, but it does not have a supporting system, which poses problems emerging from data redundancies and data loss. Among the problem is the difficulty for administrators in summarizing data of members who have transactions. To solve the problem, we devised and implemented a decision support system using the CPI (Composite Performance Index) method. The criteria are the amount of balance and active saving during a six-month interval. The results of this research is a web-based decision support system that produces a ranking order of members, which helps in selecting the best member.